Characterization of cerebral blood flow during open cardiac massage in swine: Effect of volume status - Patel, Neerav; Edwards, Joseph; Abdou, Hossam; Stonko, David P.; Treffalls, Rebecca N.; Elansary, Noha N.; Ptak, Thomas; Morrison, Jonathan J. (Frontiers in Physiology, 2022)
Introduction: Patients in cardiac arrest treated with resuscitative thoracotomy and open cardiac massage (OCM) have high rates of mortality with poor neurological outcomes. The aim of this study is to quantitate cerebral perfusion during OCM using computed tomography perfusion (CTP) imaging in a swine model of normo- and hypovolemia. Methods: Anesthetized swine underwent instrumentation with right atrial and aortic pressure catheters. A catheter placed in the ascending aorta was used to administer iodinated contrast and CTP imaging acquired. Cerebral blood flow (CBF; mL/100g of brain) and time to peak (TTP; s) were measured. Animals were then euthanized by exsanguination (hypovolemic group) or potassium chloride injection (normovolemic group) and subjected to a clamshell thoracotomy, aortic cross clamping, OCM and repeated CTP. Data pertaining to peak coronary perfusion pressure (pCoPP; mmHg) were collected and % CoPP >15mmHg (% CoPP; s) calculated post hoc. Results: Normovolemic animals (n=5) achieved superior pCoPP compared to the hypovolemic animals (n=5) pCoPP (39.3 vs 12.3, p<0.001) and % CoPP (14.5  1.9 vs 30.9  6.5, p<0.001). CTP acquisition was successful and TTP elongated from spontaneous circulation, normovolemia to hypovolemia (5.7 vs 10.8 vs 14.8, p=0.01). CBF during OCM was similar between hypovolemic and normovolemic groups (7.5  8.1 vs 4.9  6.0, p =0.73) which was significantly lower than baseline values (51.9  12.1, p<0.001). Conclusion: OCM in normovolemia generates superior coronary hemodynamics compared to hypovolemia. Despite this, neither generates adequate CBF as measured by CTP, compared to baseline. To improve the rate of neurologically intact survivors, novel resuscitative techniques need to be investigated that specifically target cerebral perfusion as existing techniques are inadequate.